Regulating charitable organisations in Malaysia: challenges and recommendations - Ali, Zuraidah; Hassan, Halyani (UPM Press, 2017)
Charities in Malaysia are regulated by aa few Acts which has its origins in the English law, whereby the concept and purpose of the charity has its origin in the Preamble to Charitable Uses Act 1601. In England and Wales, the prevailing Act on charity is the Charities Act 2011, in which 12 types of charities are acknowledged. The English Charities Act gives power to the courts and the Charity Commissioners to regulate and enforce charitable purposes in order to prevent abuses. In Malaysia, there is no single regulator or monitoring body that oversees these charitable organisations which has led to rampant abuses reported in charity organisations. This paper proposes a uniform law and procedure relating to charitable organisations and a competent body to deal with matters exclusively related to charities within the purview of local legislation, society and customs in Malaysia.